Empowerment en el rendimiento laboral en la cooperativa de ahorro y crédito Sumak Kawsay del cantón La Maná, año 2023. - Guarochico Porras, Shirley Silvana (2023)
The present investigation arose from the importance of proposing empowerment strategies that allow measuring work performance, since the cooperative does not have tools to measure its collaborators. The same one objective was to analyze the work performance of the collaborators of the SUMAK KAWSAY Savings and Credit Cooperative, through the application of the Empowerment tool in the La Maná Agency in the year 2023.The type of study was field with documentary support, based on information from key informants, who were selected according to the criteria established by the researchers and was applied to 20 of the collaborators who have information on the social reality studied. To collect the information, the survey was transmitted as an instrument, taking into account the following parameters. Inclusive organizational culture, Leadership and empowerment, autonomy and decision making, skills development and effective communication. After the application of the instruments, the results were tabulated and processed, finding as a result the problem that exists in the institution, the lack of leadership and training for employees in decision-making, for which 5 empowerment strategies were presented that allow measuring and at the same time improving work performance between the different areas operational and meet the common objectives of the institution achieving a high development and growth in financial services.